2019
DOI: 10.1137/18m1187039
|View full text |Cite
|
Sign up to set email alerts
|

Integral Equation Methods for Electrostatics, Acoustics, and Electromagnetics in Smoothly Varying, Anisotropic Media

Abstract: We present a collection of well-conditioned integral equation methods for the solution of electrostatic, acoustic or electromagnetic scattering problems involving anisotropic, inhomogeneous media. In the electromagnetic case, our approach involves a minor modification of a classical formulation. In the electrostatic or acoustic setting, we introduce a new vector partial differential equation, from which the desired solution is easily obtained. It is the vector equation for which we derive a well-conditioned in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…It will also be useful to define the wavenumber k = ω √ µ. In the most general case, the material parameters are allowed to be spatially dependent tensors [38]. There are two canonical boundary value problems in classical electromagnetics, that of scattering from perfect electric conductors (PECs) and scattering in non-conducting (dielectric, or penetrable) materials with piecewise constant material properties.…”
Section: Introductionmentioning
confidence: 99%
“…It will also be useful to define the wavenumber k = ω √ µ. In the most general case, the material parameters are allowed to be spatially dependent tensors [38]. There are two canonical boundary value problems in classical electromagnetics, that of scattering from perfect electric conductors (PECs) and scattering in non-conducting (dielectric, or penetrable) materials with piecewise constant material properties.…”
Section: Introductionmentioning
confidence: 99%
“…In general we can write the solution as a sum of two terms: E = E inc +E scat , H = H inc +H scat the incoming field and the scattered field where the incoming field E inc , H inc verifies the free space Maxwell's equations and the scattered field E scat , H scat verifies the radiation condition at infinity. This problem can be reformulated by a volume integral equation (see [4]). In this paper we will consider z-invariant geometries with TE waves and µ(x) = µ 0 .…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…In all cases we need a fast and efficient convolution with the free-space Green's function algorithm. In this paper we apply the recently developed method (see [3] [4]) to analyze homogeneous and inhomogeneous lens problems.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, most solvers involving the Helmholtz kernel are devoted to the numerical solution of the Lippmann-Schwinger integral equation [13, page 216]. While we do not intend to review all such work here, some recent contributions in this direction can be found in [1,2,5,6,10,14,15,17,21,22,24,25] and references therein. To the best of our knowledge, none of the methods cited above are designed to handle the more general class of weakly singular kernels.…”
Section: Introductionmentioning
confidence: 99%